Psychosocial interventions based on Islamic spirituality for the mental health of landslide survivors - Farmawati, Cintami; Zulfa, Nadhifatuz (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
The landslide disaster that occurred in January 2025 in Batang Regency, Central Java, had multidimensional impacts, encompassing physical, social, and psychological losses. Initial assessments indicated that many survivors experienced difficulty sleeping, anxiety, profound sadness, and loss of motivation, indicating post-disaster mental health disorders. If left untreated, these conditions can reduce the quality of life and hinder the psychosocial recovery process of affected communities. This study aimed to improve the mental health of landslide survivors through psychosocial interventions based on Islamic spirituality. A concurrent embedded approach method was used. There were five participants in the study, selected through purposive sampling. The intervention was administered in groups for five sessions. Before and after the intervention sessions, researchers conducted pre- and post-tests using Brief Mental Health Inventory (BMHI-12) which were analyzed using the Wilcoxon signed-rank test statistical technique. Data from interviews and observations were analyzed qualitatively. The results of the Wilcoxon signed-rank test showed a value of 0.043 < 0.05, where the significant value < 0.05 means that providing psychosocial interventions based on Islamic spirituality effective in improving mental health of the five research participants. Psychosocial interventions based on Islamic spirituality significantly help participants in expressing feelings, managing emotions, constructing meaning from disasters, and strengthening social relationships, so that they can be an applicable model in the context of Islamic psychology and psychosocial disaster response.